Evaluation of Spiritual Health in Nursing and Midwifery school students of Ilam University of Medical Sciences According to Islam - Imanzad, masoumeh; Tavan, hamed; Taghinejad, hamid; Mousavi Moghadam, rahmatollah; Sayehmire, kourosh (Advances in Nursing & Midwifery, 2013)
Abstract Introduction: From the view point of holistic nursing, human body is multi-dimensional and while he has the cognitive, emotional, social and spiritual dimensions; the spiritual dimension is superior to others. Greater the spiritual health of nursing students increases, they will be better able to care for patients, so we did this study for evaluation of spiritual health among nursing students. Materials and Methods: In a descriptive- correlation study and according to the view of Islam, a questionnaire about spiritual health that consists of the following sections: demographic information, the belief system, mentality dimension, the morality system and lifestyle, respectively is distributed between 100 nursing students using simple random selection. The collected responds are analyzed by the SPSS software and the results of spiritual health are divided into four levels from low to high level. Results: 61% of the samples were male. None of them scored low level. 4%, 53% and 43% of the samples achieved the levels of low-moderate, moderate to high and high-level, respectively. The results showed significant relationship between spiritual health aspects with age and sex. Conclusion: We didn’t find any statistical relationship between the spiritual health and the semester; so, it seems that education has no effect on the spiritual health of college students. Hence, to promote the spiritual health of college students, we suggest adding a course about the spiritual health at four-year program of nursing education content. Keyword: Spiritual Health, College, Students, Nursing, Islam